Montessori Junior High School Students’ Perceptions on Their Self-Efficacy in Reading - Niko Albert Setiawan; Ouda Teda Ena (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
Montessori approach deals with learning in independence and liberty. This way of learning requires students to explore information based on their learning interest. Therefore, reading has become one of the keys in learning successfully in a Montessori school. Moreover, the impact of self-efficacy on the learning outcomes has been explored in the educational psychology as a field of study. This study inspects students’ self-efficacy perceptions and their factors in reading comprehension in a Montessori Junior High School registered in 2018-2019 academic year. It is located in Yogyakarta, Indonesia. English is the main language used in the teaching-learning process in the school. The study is conducted by using mixed method. Findings are based on the 27 close-ended questions and three open-ended questions obtained from the students in grade seven and eight. In analyzing the results, concurrent triangulation strategy is applied. The results show that the students have positive self-efficacy perceptions on their reading (Average= 3.449/5), especially in reading, explaining, summarizing texts and comprehending the graphics found in the text without the guidance of their teachers. Their self-efficacy sources are found in their mastery experiences, vicarious experiences, verbal persuasion, and emotional and psychological states.